Transformation and Absolute Convergence of Trigonometric Fourier Series - Temirgaliyev, Н. (Bulletin of L.N. Gumilyov Eurasian National University. Mathematics, computer science, mechanics series, 2019)
The article is devoted to the problems of the theory of summability and absolute convergence of trigonometric Fourier series with the formulation of problems belonging to P.L. Ulyanov, in the context of the further development of these areas of research.